Effectiveness of vestibular rehabilitation in elderly subjects with dizziness - Berticelli, Amanda Zanatta (2016)
This study aimed to verify the effectiveness of the vestibular rehabilitation (VR) exercises in elderly with dizziness. Method: evaluations of the balance were performed before and after vestibular rehabilitation. Results: 36 elderly were evaluated. By comparing pre and post rehabilitation scores, we observed significant improvement post rehabilitation. Conclusion: the vestibular rehabilitation is an effective therapeutic procedure in the elderly who have been suffering from dizziness. Keywords:  Aged; Dizziness; Postural balance.